ASPEK PENEGAKAN HUKUM DALAM PENERTIBAN RUMAH NEGARA SEBAGAI IMPLEMENTASI KEBIJAKAN PENGELOLAAN DI BADAN RISET DAN INOVASI NASIONAL - Taswin Taswin (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Government Regulation Number 40 of 1994 states that a state house is "a building that is owned by the state and functions as a residence or shelter and a means of family development as well as supporting the implementation of the duties of Officials and/or Civil Servants". There are 1,198 state houses owned by the National Research and Innovation Agency, consisting of 930 landed houses and 268 flats. Of the total state houses owned by BRIN, 360 state houses in the form of landed houses are occupied by unauthorized residents. From this data it can be seen that there is still disorder in the occupancy of state houses, especially landed houses. The research method used is a normative juridical approach to explore the applicable provisions and a descriptive approach to assess how law enforcement is implemented regarding this disorder. The steps taken by BRIN in enforcing the law and optimizing management include strengthening the legal basis for management policies, strengthening institutions, disseminating legal regulations, and carrying out control over state houses occupied by unauthorized parties. The application of law enforcement prioritizes using a persuasive approach, except in certain cases and conditions. The results of law enforcement in controlling state houses have shown results, although they are not yet optimal